ORF6 and ORF61 Expressing MVA Vaccines Impair Early but Not Late Latency in Murine Gammaherpesvirus MHV-68 Infection - Samreen, Baila; Tao, Sha; Tischer, Karsten; Adler, Heiko; Drexler, Ingo (Frontiers in Immunology, 2019)
Gammaherpesviruses (HV) are important pathogens causing persistent infections which lead to several malignancies in immunocompromised patients. Murine HV 68 (MHV-68), a homolog to human EBV and KSHV, has been employed as a classical pathogen to investigate the molecular pathogenicity of HV infections. HV express distinct antigens during lytic or latent infection and antigen-specific T cells have a significant role in controlling the acute and latent viral infection, although the quality of anti-viral T cell responses required for protective immunity is not well understood. We have generated recombinant modified vaccinia virus Ankara (recMVA) vaccines via MVA-BAC homologous recombination technology expressing MHV-68 ORF6 and ORF61 antigens encoding both MHC class I and II-restricted epitopes. After vaccination, we examined T cell responses before and after MHV-68 infection to determine their involvement in latent virus control. We show recognition of recMVA- and MHV-68-infected APC by ORF6 and ORF61 epitope-specific T cell lines in vitro. The recMVA vaccines efficiently induced MHV-68-specific CD8+ and CD4+ T cell responses after a single immunization and more pronounced after homologous prime/boost vaccination in mice. Moreover, we exhibit protective capacity of prophylactic recMVA vaccination during early latency at day 17 after intranasal challenge with MHV-68, but failed to protect from latency at day 45. The data support further efforts aiming at improved vaccine development against HV infections with special focus on targeting protective CD4+ T cell responses.